Systematic literature review on innovation capabilities in clusters (INMR - Innovation & Management Review, 2021)
Purpose – This paper aims to map literature about innovation capabilities (IC) taking into considerationindustrial clusters to propose a conceptual framework that synthetizes the main factors and subfactorsresponsible for ICs; in addition, the paper also proposes a research agenda.Design/methodology/approach – A systematic literature review (SLR) was performed; academicpapers were analyzed qualitatively and quantitatively.Findings – The authors provide a descriptive analysis followed by a thematic synthesis, in which wepresent 05 enablers and 20 critical factors (CF) of IC in clusters. The proposed framework emphasizes whatneeds to be done or improved to increase IC in cluster-based companies. Based on this systematic review andthe framework proposed, the authors identified opportunities for future research.Research limitations/implications – The enablers and CF identified through SLR were not validatedempirically. Therefore, future studies on the current topic are required to validate the framework byinvestigating which factors are more relevant to cluster-based companies that intend to improve theirinnovative performance.Practical implications – The present findings have important implications for the identification of thefactors and subfactors that may contribute to the development of IC, which may help managers and decisionmakers in recognizing which factors are the most responsible for business innovation.Originality/value – The paper identifies enablers related to the development of IC in industrial cluster andpresents a research agenda. The framework represents a guideline for companies to achieve better innovationperformance.